A Narrative Inquiry: Students Perception in Increasing Teachers’ Identity By Join Microteaching - Setiyorini, Febri Ayu; Prihatin, Yoga; Santoso, Masfuad Edi (South Asian Journal of Social Sciences and Humanities, 2021)
Teaching is the process of focusing on people’s needs, experiences, and feelings. It makes the  students learning new things for their future. Microteaching can be one of ways to help the students  of teacher training and education to improve their teaching skills to be suitable with required  qualifications and building up their teachers’ identity. This research aims to know what the  students of the 8th semester English Department’s perceptions on microteaching related to their  teaching practicum by using questionnaire and interview. Testing the validity and reliability of  questionnaire uses correlation product moment SPSS. From fifteen questions, one question is  invalid. Meanwhile, the results of this research are students of 8th semester English Department  agree that microteaching is effective to build up their teaching competences and ability.
Keywords: Microteaching; Teaching competencies; Students perceptions